Challenging Facial Recognition systems before Courts. From and Beyond ECtHR Glukhin v. Russia (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The Article examines the first judgment delivered by the European Court of Human Rights against Russia on the use of facial recognition systems, finding a violation of Articles 8 and 10 ECHR. The Article frames the discussion in the context of the recent developments in the regulation of artificial intelligence technologies, alongside a comparative analysis of a number of judgments issued by a selection of European and non-European States. The paper highlights the approach of the EDU Court towards the use of biometric identification systems to verify whether, and to what extent, these systems comply with the fundamental rights set forth under the European Convention.
Keywords: Facial Recognition; European Court of Human Rights; Private Life; Interference; Risks